Welcome :: Homework Help and Answers :: Mathskey.com

Recent Visits

    
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,282 questions

17,801 answers

1,438 comments

34,118 users

Solve the exponential equation

0 votes

6^(4x - 2) = 11^(X + 2)

asked Dec 28, 2017 in ALGEBRA 2 by anonymous
reshown Dec 28, 2017 by bradely

1 Answer

0 votes

6^(4x - 2)   =   11^(X + 2)

Apply logorithm to each side

log[6^(4x - 2)]   =   log[11^(X + 2)]

(4x - 2) log 6   =   (x + 2) log 11

(4x) log 6 - 2 log 6   =   log 11+ 2 log 11

(4x) log 6 log 11   =   log 11 + log 6

x[ 4 log 6  log 11]   =    log (11^2) +  log (6^2)

x[ log 1296 -  log 11]   =    log (121 * 36)

x[ log (1296/11)]   =    log 4356

x   =    [ log (4356) ] / log (1296/11)]

answered Dec 28, 2017 by homeworkhelp Mentor

Related questions

asked Dec 28, 2017 in ALGEBRA 2 by anonymous
asked Dec 28, 2017 in ALGEBRA 2 by anonymous
asked Jan 29, 2015 in CALCULUS by anonymous
...